Cadmium inhibits neural stem/progenitor cells proliferation via MitoROS‐dependent AKT/GSK‐3β/β‐catenin signaling pathway. Issue 12 (11th May 2021) - Luo, Huan; Song, Bo; Xiong, Guiya; Zhang, Bing; Zuo, Zhenzi; Zhou, Zhijun; Chang, Xiuli
Abstract: Cadmium (Cd) is a toxic heavy metal widely found in the environment. Cd is also a potential neurotoxicant, and its exposure is associated with impairment of cognitive function. However, the underlying mechanisms by which Cd induces neurotoxicity are unclear. In this study, we investigated the in vitro effect of Cd on primary murine neural stem/progenitor cells (mNS/PCs) isolated from the subventricular zone. Our results show that Cd exposure leads to mNS/PCs G1/S arrest, promotes cell apoptosis, and inhibits cell proliferation. In addition, Cd increases intracellular and mitochondrial reactive oxygen species (ROS) that activates mitochondrial oxidative stress, decreases ATP production, and increases mitochondrial proton leak and glycolysis rate in a dose‐dependent manner. Furthermore, Cd exposure decreases phosphorylation of protein kinase B (AKT) and glycogen synthase kinase‐3 beta (GSK3β) in mNS/PCs. In addition, pretreatment mNS/PCs with MitoTEMPO, a mitochondrial‐targeted antioxidant, improves mitochondrial morphology and functions and attenuates Cd‐induced inhibition of mNS/PCs proliferation. It also effectively reverses Cd‐induced changes of phosphorylation of AKT and the expression of β‐catenin and its downstream genes. Taken together, our data suggested that AKT/GSK3β/β‐catenin signaling pathway is involved in Cd‐induced mNS/PCs proliferation inhibition via MitoROS‐dependent pattern. Abstract : Cd exposure induces inhibition of mNS/PCs proliferation. Cd activates mitochondrial oxidative stress and causes abnormalities in mitochondrial function and morphology. Besides, AKT/GSK‐3β/β‐catenin signaling pathway involves in Cd‐induced inhibition of mNS/PCs proliferation. MitoTEMPO attenuates Cd‐induced inhibition of mNSCs proliferation.